Effectiveness of taping on functional performance in elite athletes: A systematic review - Lau, K. K.-L.; Cheng, K. C.-C. (Journal of Biomechanics, 2019)
Taping has been showing its effect on the rehabilitation aspect with numerous reviews. However, there is lack of evidence on the effect of taping on functional performance, espectially in elite sports settings. This review aimed to evaluate the effectiveness of taping intervention on sports-related functional performance among the elite athlete population. Online databases such as Ovid MEDLINE, ProQuest, PubMed, ScienceDirect, Scopus, SPORTDiscus, and Web of Science were searched. Eligibility criteria were listed as follows: (i) English, (ii) academic journal, (iii) research article, (iv) elite or professional athletes, (v) experimental research design, (vi) sport, (vii) taping, and (viii) functional performance. Specific emphases were targeted on within-subject comparison and healthy subjects. The PEDro scale was utilized for appraising on the statistical information, as well as internal and external validity. The Cohen's d effect size with 95 percent confidence intervals was used to compare taped versus not-taped condition. Nine studies were included in this review and 25 comparisons were extracted. Positive effects were found on balance performance with rigid tape, and horizontal jump performance with elastic tape. Alternatively, negative effects were found on vertical jump performance. An interesting finding was noted on the effect of taping applied after 24?h. Overall, taping could be a beneficial practice for elite sports performance.